Partisanship and personal vote-seeking in parliamentary behaviour - Fleming, TG (2020)
Incumbent politicians can use parliamentary behaviour to generate a 'personal vote': electoral support attracted to an individual candidate rather than their party label. This personal vote-seeking has consequences for accountability, representation, and policymaking, yet its prevalence varies extensively. Existing explanations of this variation focus on the consequences of electoral institutions and the characteristics of individual members of parliament (MPs). This thesis adds to a much smaller literature linking MPs' personal vote-seeking to characteristics of its intended audience: voters. Specifically, I argue that partisanship among voters reduces MPs' incentives for engaging in personal vote-seeking, by limiting its effectiveness. When voters have stronger ties to political parties, they are less likely to reward or punish MPs for their individual qualities and performance. As a consequence, lower partisanship among citizens should lead to more extensive personal vote-seeking by MPs. I test this argument in two stages. First, I test its voter-level implications. Using a quasi-experiment in New Zealand and a survey experiment in the United Kingdom (UK), I find evidence that partisanship does make voters less likely to reward MPs for their individual behaviour in parliament. Second, I test its MP-level implications. Analysing legislative behaviour in the UK House of Commons, I find evidence that MPs' personal vote-seeking efforts can be linked to variation in voters' partisanship over time, and (less consistently) between constituencies. Taken together, these findings offer new evidence that voters' relationships with political parties shape MPs' electoral strategies and parliamentary behaviour. This suggests an important link between how voters think about politics, and how their representatives conduct it.